Regrets? I've had a few, but then again-- : towards a psychology of regret : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Psychology at Massey University - Bloore, David John (Massey University, 2003)
The aim of the present study was to investigate the experience of regret and how regret affects people's lives. A convenience sample of 101 adult volunteers (mean age 32.5) completed a questionnaire, which measured the content of regret, the emotional profiles of action and inaction regret, the temporal pattern of regret and the relationship between regret and life satisfaction. Results showed that personal responsibility was an important aspect of most regret experiences. Contrary to the hypothesis and previous research, there was no difference in the number of action and inaction regrets reported by the participants. Previous research claims regrets of inaction are more frequent and more significant than regrets of action. As predicted, action regrets were experienced more recently than inaction regrets, thus providing indirect evidence for the 'temporal pattern' theory of regret. However, other results indicated that action and inaction regrets have different emotional profiles and that characteristic differences may cause this 'temporal pattern'. It is recommended that a longitudinal study be conducted in this area of regret research. The main content areas of the participants' regrets were for intimate relationships, family, education and health/self-care, as found in previous research. Some content differences were found for action/inaction and gender; there were no age differences however. Consistent with the hypotheses, the number of regrets, the intensity of regrets, the frequency of regret thought and the impact of regret were all negatively correlated with life-satisfaction. Participants whose regrets had a positive impact were also more satisfied with their lives. Thus, the present research suggests that regret can have a constructive function. Based on these findings, a number of suggestions are outlined to help minimise the negative effects of regret. These include, accepting one's past mistakes, using past regrets as learning experiences and minimising the amount of time spent thinking about regret.
Keywords: Regret